Autophagy impairment in a mouse model of neuropathic pain - Berliocchi Laura; Russo Rossella; Maiarù Maria; Levato Alessandra; Bagetta Giacinto; Corasaniti Maria (SAGE Publishing, 2011)
Abstract Autophagy is an intracellular membrane trafficking pathway controlling the delivery of cytoplasmic material to the lysosomes for degradation. It plays an important role in cell homeostasis in both normal settings and abnormal, stressful conditions. It is now recognised that an imbalance in the autophagic process can impact basal cell functions and this has recently been implicated in several human diseases, including neurodegeneration and cancer. Here, we investigated the consequences of nerve injury on the autophagic process in a commonly used model of neuropathic pain. The expression and modulation of the main autophagic marker, the microtubule-associated protein 1 light chain 3 (LC3), was evaluated in the L4-L5 cord segment seven days after spinal nerve ligation (SNL). Levels of LC3-II, the autophagosome-associated LC3 form, were markedly higher in the spinal cord ipsilateral to the ligation side, appeared to correlate with the upregulation of the calcium channel subunit α2δ-1 and were not present in mice that underwent sham surgery. However, LC3-I and Beclin 1 expression were only slightly increased. On the contrary, SNL promoted the accumulation of the ubiquitin- and LC3-binding protein p62, which inversely correlates with autophagic activity, thus pointing to a block of autophagosome turnover. Our data showed for the first time that basal autophagy is disrupted in a model of neuropathic pain.